2021
DOI: 10.3389/fpsyt.2020.531571
|View full text |Cite
|
Sign up to set email alerts
|

Premature Birth and Developmental Programming: Mechanisms of Resilience and Vulnerability

Abstract: The third trimester of pregnancy represents a sensitive phase for infant brain plasticity when a series of fast-developing cellular events (synaptogenesis, neuronal migration, and myelination) regulates the development of neural circuits. Throughout this dynamic period of growth and development, the human brain is susceptible to stress. Preterm infants are born with an immature brain and are, while admitted to the neonatal intensive care unit, precociously exposed to stressful procedures. Postnatal stress may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 313 publications
2
45
0
Order By: Relevance
“…Studies that examined NNS + tucking found preterm infants experienced relief only for mild‐ or short‐term pain (Cignacco et al, 2012; Liaw, Yang, Wang, et al, 2012). However, heel‐stick procedures are both intrusive and painful to preterm infants (Lammertink et al, 2021) requiring the infant's heel to be held and squeezed for 2–3 min to collect 5–6 microtubes of blood. The design of modulating the infant's behavioral state and providing NNS and tucking was based on the findings of Yin et al (2015) who demonstrated that BSM was effective at reducing the trauma of a painful procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that examined NNS + tucking found preterm infants experienced relief only for mild‐ or short‐term pain (Cignacco et al, 2012; Liaw, Yang, Wang, et al, 2012). However, heel‐stick procedures are both intrusive and painful to preterm infants (Lammertink et al, 2021) requiring the infant's heel to be held and squeezed for 2–3 min to collect 5–6 microtubes of blood. The design of modulating the infant's behavioral state and providing NNS and tucking was based on the findings of Yin et al (2015) who demonstrated that BSM was effective at reducing the trauma of a painful procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Procedural pain from diagnostics in the NICU, such as heel pricks, ventilation, and venous blood sampling, and non‐painful experiences, which include cluster caregiving, position change, administration of medicine, weighing, and tube removal, also cause disequilibrium in preterm infants (Liaw, Yang, Hua, et al, 2012; Newnham et al, 2009). For preterm infants in the NICU, there are three main sources of stress: physical stress, which includes repetitive procedural pain from a heel prick; environmental stress, such as noise, light, and caregiving events; and maternal stress, such as long periods of separation from the mother (Lammertink et al, 2021). Therefore, for the purposes of this study, we have defined stress related to painful procedures as procedural pain‐related stress.…”
Section: Introductionmentioning
confidence: 99%
“…Following preterm delivery, the environmental situation changes significantly from the intrauterine environment to the extrauterine environment. The hospitalization and pain-related events due to medical procedures (acute procedural, and acute prolonged) expose the child to several sources of stress, such as environmental stress, as well as atypical maternal care [23]. Environmental stress is linked to noncyclical and bright light exposure, loud noises (many times exceeding the recommended sound level of 45 dB), gravitational forces, frequent handling, or cool and dry temperature.…”
Section: Potential Mechanisms: Hypothalamic-pituitary-adrenal Axis Autonomic Nervous System and Co-regulationmentioning
confidence: 99%
“…Among the risk factors for adrenal insufficiency are gestational age below 30 weeks, early postnatal age, perinatal stress (linked with the stressful situations and postnatal illness), and duration of corticosteroid use [24]. Lammertink and colleagues [23] suggest that the impact of prematurity provides long-lasting changes in HPA-functioning, while the timing of the stressor plays a fundamental role to the type and magnitude of the stress-responses in preterm babies, as well as that it might contribute to a differential impact and reaction (as hypo-or hyper-reactivity).…”
Section: The Hypothalamic-pituitary-adrenal Axis and The Preterm Infant's Behavioral Statementioning
confidence: 99%
“…Moreover, during the neonatal period, neuronal pathways are immature and are therefore particularly vulnerable [ 37 ]. Exposition to stress and multisensory dystimulation during this period can induce long term impacts on developmental outcomes, including brain development, stress regulation system and adjustment problems [ 29 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%